Wished - Evans, Lissa ca. 20. Jh (David Fickling Books, 2022)
Ed and his sister Roo are faced with the most boring half-term holiday in history: five days spent in the company of their elderly neighbour Miss Filey, and her ancient, smelly cat. But when they find a box of birthday candles in a cupboard in Miss Filey's house, their world is changed completely. These are no ordinary candles, every single one of them comes with a wish. There's only one problem: some of those wishes actually belong to someone else
Keywords: Siblings / Juvenile fiction; Holidays / Juvenile fiction; Neighbors / Juvenile fiction; Children with disabilities / Juvenile fiction; Candles / Juvenile fiction; Wishes / Juvenile fiction; Cats / Juvenile fiction; Magic / Juvenile fiction; Frères et surs / Romans, nouvelles, etc. pour la jeunesse; Voisins / Romans, nouvelles, etc. pour la jeunesse; Enfants handicapés / Romans, nouvelles, etc. pour la jeunesse; Souhaits / Romans, nouvelles, etc. pour la jeunesse; Children's stories; Humorous fiction; Juvenile works; Kinderbuch